Methodology for Assessing the Consumption of Tourism Services in Regional Markets - CHUMAKOVA, Olga V. (Journal of Environmental Management and Tourism, 2019)
The paper presents aspects of regulation of consumption of tourist services in regional markets. In General, the differences in understanding the essence of the domestic market in Russia and the EU are shown. For each structure, the regional market is primarily an opportunity to attract additional funding and provide opportunities for business development. The authors actualize the conceptual apparatus of institutional development and demand for tourism services. The subject of the study is the formation of economic and marketing formation of consumption of domestic tourism product. The novelty of the study lies in the fact that for the first time in domestic science analyzed the possible demand for domestic tourism product, which is identified with foreign territories and provided by the development of appropriate infrastructure and a set of specific indicators that can ensure the further development of not only domestic tourism, but also its improvement to the international level. The further direction of research can be considered the development of spatial relations and the formation of the principles of public-private partnership, when each of the participants in public relations creates opportunities for institutional development of the territories themselves and the gradual allocation of tourism-oriented regional economic complexes. The possibilities of international cooperation of the country's regions are proposed